2019
DOI: 10.1021/acsapm.9b00813
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Printing with Waste High-Density Polyethylene

Abstract: Fused filament fabrication (FFF) three-dimensional (3D) printing of semicrystalline polymers such as high-density polyethylene (HDPE) is challenging because crystallization-induced shrinkage of the filament, as it cools, results in stresses that warp the printed part and debond it from the print substrate. Here, we demonstrate that waste-derived HDPE can be successfully 3D printed by (i) blending with a small fraction (<0.5% by weight) of dimethyl dibenzylidene sorbitol (DMDBS) and (∼10%) linear low density po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 48 publications
0
27
0
Order By: Relevance
“…Conversion of waste-derived high-density polyethylene to three-dimensional (3D) printing filament has important technological implications. A facile strategy to expand the palette of waste-derived polymer materials for fused filament fabrication (FFF) three-dimensional (3D) printing was explained in details (Gudadhe et al 2019 ). The polymer–matrix composites based on recycled high-density polyethylene with either lead oxide nanoparticles or lead oxide bulk using 10 and 50% weight fractions were synthesized by solid-state intermixing and thermal pressing technique.…”
Section: Polymer Composites For Gamma-radiation Shieldingmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversion of waste-derived high-density polyethylene to three-dimensional (3D) printing filament has important technological implications. A facile strategy to expand the palette of waste-derived polymer materials for fused filament fabrication (FFF) three-dimensional (3D) printing was explained in details (Gudadhe et al 2019 ). The polymer–matrix composites based on recycled high-density polyethylene with either lead oxide nanoparticles or lead oxide bulk using 10 and 50% weight fractions were synthesized by solid-state intermixing and thermal pressing technique.…”
Section: Polymer Composites For Gamma-radiation Shieldingmentioning
confidence: 99%
“…The mechanical behavior of the composite after adding various wt% of graphite powder (GP 10 weight %), TiO 2 (10 weight %), and modified clay CLOISITE 30B revealed that by addition of graphite powder or titanium dioxide (TiO 2 ), the composite showed better tensile properties (Marinkovic et al 2013 ). By incorporating O-hydroxybenzene diazonium chloride (OBDC), silane, and glycidyl methacrylate (GMA) in sisal fiber-reinforced recycled polypropylene composites, the mechanical properties of the composite were preferably enhanced by O-hydroxybenzene diazonium chloride (OBDC)/recycled polypropylene composites (Gupta et al 2014 ). Various amounts of clay content (Cloisite 10A 1 to 6 weight %) were added to recycled polyethylene terephthalate/clay nanocomposites.…”
Section: Polymer Composites For Gamma-radiation Shieldingmentioning
confidence: 99%
“…Kumaraswamy and coworkers modified the shrinkage of high density polyethylene melts upon cooling induced by crystallization via the addition of B0.4% dimethyl dibenzylidene sorbitol and B10% of linear low density polyethylene. 206 With this modification, the warpage of high density polyethylene in a three-dimensional printing process is significantly minimized. This approach was even applicable for recycled polymers that were processed at least one time before use in the 3D printing process.…”
Section: Linear Polymers With Controlled Moderate Degrees Of Branchingmentioning
confidence: 99%
“…For melting/extrusion based 3D printing processes, the majority of current research involves eco‐friendly materials, such as thermoplastic polylactic acid (PLA), [ 21 ] hemicellulosic biopolymers extracted from lignocellulosic agricultural wastes, [ 22 ] and recycled waste‐derived high‐density polyethylene (HDPE). [ 23 ] Very recently, soybean oil methacrylates [ 24 ] and highly functional bio‐based (meth)acrylate resins synthesized from epoxidized sucrose soyate [ 25 ] have been applied as photopolymer resins for commercial SLA printers.…”
Section: Introductionmentioning
confidence: 99%